Changes in Cellular Morphology in Bronchoalveolar Lavage Fluid of Children with Mycoplasma Pneumoniae Pneumonia - Ma Kun; Li Shujun (Journal of Public Health International, 2024)
Objective To study changes of cell morphology in BALF in children with Mycoplasma pneumoniae pneumonia (MPP). Methods From December 2021 to May 2022, a group of 32 children diagnosed with Acute MPP and admitted for treatment in the Pediatrics Department and PICU of the First Affiliated Hospital of Xinxiang Medical University were selected for our study. These patients underwent bronchoalveolar lavage as part of their clinical assessment. For comparison, we included a control group comprising 10 children who were not infected but had bronchial foreign bodies. We investigated the cellular composition in the bronchoalveolar lavage fluid (BALF) using Wright-Giemsa staining and microscopic evaluation, aiming to understand the relationship between shifts in cell proportions and extra-pulmonary symptoms associated with MPP. Results In this study, a total of 42 cases were enrolled, with 32 cases in the study group and 10 cases in the control group. There were no statistically significant differences in gender, age, height, weight, and BMI between the two groups (p > 0.05). The study group exhibited significantly higher levels of neutrophil percentage (GRA%), CRP, D-dimer, and LDH in blood routine tests compared to the control group (p < 0.05). Furthermore, the proportions of neutrophils (%) and macrophages (%) in BALF were significantly higher in the study group compared to the control group (p< 0.05), while the proportion of lymphocytes (%) in BALF showed no statistically significant difference between the two groups (p> 0.05). Conclusion In the acute phase of MPP in children, BALF is predominantly composed of neutrophils. A lower proportion of lymphocytes in BALF is associated with a higher incidence of extra-pulmonary manifestations and longer hospitalization duration.
Keywords: cytological morphology